Thackeray : the major novels - McMaster, Juliet (Canadian university paperbooks, 1976)
Although few critics deny Thackeray's position as a major novelist, he has had comparatively little of the kind of critical attention that has been devoted to Jane Austen, Charles Dickens, George Eliot, or Henry James in the last thirty years. His curious combinations of satire and sentiment, geniality and deviousness, snobbery and anti-snobbery, and his habits of retreating from one disguise to another, have made him difficult to deal with, and his practice of exposing his stories as fictions has evoked hostility in many critics who are none the less fascinated by him. In this original and revealing study of the major novels, Juliet McMaster contends that Thackery is a consummate artist and a highly sophisticated ironist, exploiting to the full the potential of the various personae he adopts, and introducing ambiguity deliberately, to sharpen the reader's moral perceptions and to evoke the complexity of experience itself.